2015
DOI: 10.1155/2015/938054
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion and Acupuncture Ameliorate Crohn’s Disease by Regulating the Balance between Th17 and Treg Cells in the Intestinal Mucosa

Abstract: Previous studies have demonstrated that acupuncture is beneficial to patients with Crohn's disease (CD), but the mechanism underlying its therapeutic effects remains unclear. To identify the mechanism by which acupuncture treats CD, the balance between Th17 and Treg cells was assessed in CD patients. In this study, Ninety-two CD patients were randomly and equally assigned to a treatment group that were treated with herb-partitioned moxibustion and acupuncture or a control group with wheat bran-partitioned moxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…For instance, many patients, especially in China and Asia areas, try to consult traditional medical doctors to manage their conditions by acupuncture and moxibustion [ 16 ]. Up till now, reports have demonstrated that acupuncture plus moxibustion or moxibustion alone can (1) manage the symptoms of abdominal pain, diarrhea, bloody stool, and consequent weight loss [ 17 ], (2) promote recovery of damaged intestinal tissues due to inflammation [ 18 ], and (3) suppress the inflammatory response of UC [ 19 ]. However, as to the Th17/Treg, so far very few studies of acupuncture and moxibustion have direct evidence to show that they can influence the balance of these two kinds of cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many patients, especially in China and Asia areas, try to consult traditional medical doctors to manage their conditions by acupuncture and moxibustion [ 16 ]. Up till now, reports have demonstrated that acupuncture plus moxibustion or moxibustion alone can (1) manage the symptoms of abdominal pain, diarrhea, bloody stool, and consequent weight loss [ 17 ], (2) promote recovery of damaged intestinal tissues due to inflammation [ 18 ], and (3) suppress the inflammatory response of UC [ 19 ]. However, as to the Th17/Treg, so far very few studies of acupuncture and moxibustion have direct evidence to show that they can influence the balance of these two kinds of cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that electro-acupuncture and moxibustion may help to improve clinical results in CD patients through different central integration patterns. Acupuncture and moxibustion also inhibited levels of IL-17 and retinoid-related orphan receptor gamma (RORγt) but induced forkhead box P3 (FOXP3) expression in the intestinal mucosa of patients with CD [31]. In addition, herb-partitioned moxibustion combined with acupuncture induces mucosa inflammation remission and repairs the tight junction barrier structure in intestinal epithelial mucosa, increasing the expression of zonula occludens-1 mRNA [32].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture attenuated inflammation through the vagus nerve mediated by dopamine [ 43 ]. The combination of acupuncture and moxibustion relieved Crohn’s disease by decreasing the ratio of Th17 to Treg cells in the intestinal mucosa [ 44 ]. These studies support that acupuncture has not only an analgesic effect but also an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%